Investigating possible shared single nucleotide polymorphisms in isolated oral cleft and non-cleft facial morphology - Küchler, Erika Calvano; Meger, Michelle Nascimento; Pires, Bruna Correia Rauta; Beisel-Memmert, Svenja; Hemming, Daniel; Coletta, Ricardo D.; Scariot, Rafaela; Matsumoto, Mírian Aiko Nakane; Oliveira, Maria Angelica Hueb de Menezes; Kirschneck, Christian; Cavalcante-Leão, Bianca (Frontiers in Dental Medicine, 2025)
IntroductionFacial morphogenesis is regulated by several cellular interactions that are mediated by numerous morphogenetic signals. Based on the existing evidence, we hypothesize that oral cleft-associated single nucleotide polymorphisms (SNPs) are involved in the normal range of human face development. Therefore, this study aimed to investigate the association between SNPs in oral cleft-related genes and variations in the normal range of facial morphology.MethodA sample of healthy Brazilian teenagers (aged between 11 and 18 years old) were screened and collected. Frontal facial digitized photographs from orthodontic records were used to determine phenotypes, while the DNA extracted from saliva samples was used to investigate the candidate SNPs. Five oral cleft-associated SNPs in BMP2 (rs235768), BMP4 (rs17563), WNT3A (rs708111), WNT11 (rs1533767), and RUNX2 (rs1200425) were selected, and allelic discrimination analysis was performed using real-time PCR.ResultsA total of 58 individuals (27 boys and 31 girls) were included. The facial landmarks used for the facial measurements were the trichion (Tr), glabella (G), nassion (N), subnasale (Sn), labrale superior (Ls), labrale inferior (Li), gnathion (Gn), cheilon (Ch), and zygoma (Zg). rs17563 in BMP4 was associated with lip proportion, in which individuals with the homozygous GG genotype had a higher Ch-Ch:Ls-Li proportion than the heterozygous AG genotype (p = 0.034). rs1533767 in WNT11 was associated with G-Sn:Sn-Gn (p = 0.028), N-Gn:Sn-Gn (p = 0.035), and Sn-Gn:Tr-Gn (p = 0.039).ConclusionOur study supported the hypothesis that oral cleft-associated SNPs are involved in the normal range of human facial morphology.